Effect of Ultrasonic Frequency on Thickener Performance - Gongcheng Li; Shulong Liu; Zengsheng Wen; Guolei Liu; Yu Cui; Yajian Shao (Advances in Materials Science and Engineering)
Gravity thickening is an important aspect to solve numerous environmental and safety problems that were created by tailings discharging at low solid concentrations. Furthermore, in order to efficiently facilitate the separation of released water and solid sediments, a continuous thickening system with ultrasonic equipment has been used to investigate the thickening performance of copper-mine tailings under different ultrasonic frequencies (16 kHz, 20 kHz, 22 kHz, 25 kHz, and 28 kHz). After freeze-drying treatment, the underflow samples are imaged using the scanning electron microscope (SEM); then, the structure of floc or aggregates in the SEM images is quantifiably analyzed using the software of Image J. Results show that the underflow concentration increases as the ultrasonic frequency increases and decreases afterwards. A linear logarithmic function can explain the relationship between underflow concentration and run time at a certain ultrasonic. The underflow concentration is maximized at 64.47 wt. % when the ultrasonic frequency is 22 kHz. Based on the analysis on the microstructure of underflow samples, the minimum pore average size and pore average fraction are obtained when the ultrasonic frequency is 22 kHz, implying that 22 kHz is the optimum ultrasonic frequency combining the results of the underflow concentration.